2023
DOI: 10.3390/jcm12062192
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue: A Piece of The Puzzle in Pediatric Hypertension

Abstract: Background and purpose: Epicardial adipose tissue (EAT) is a metabolically active tissue located on the surface of the myocardium, which might have a potential impact on cardiac function and morphology. The aim of this study was to evaluate whether EAT is associated with essential arterial hypertension (AH) in children and adolescents. Methods: Prospective cardiovascular magnetic resonance (CMR) study and clinical evaluation were performed on 72 children, 36 of whom were diagnosed with essential AH, and the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several studies have also shown a correlation between EAT and essential high blood pressure in children with obesity and particularly those with MS [33,34]. Schweighofer et al [35] also showed a significant association between essential hypertension and EAT in non-obese children, which leads to the question of whether the amount of EAT could be partly influenced by genetic factors and suggests a potential role for EAT in the development of hypertension.…”
Section: Children With Obesitymentioning
confidence: 99%
“…Several studies have also shown a correlation between EAT and essential high blood pressure in children with obesity and particularly those with MS [33,34]. Schweighofer et al [35] also showed a significant association between essential hypertension and EAT in non-obese children, which leads to the question of whether the amount of EAT could be partly influenced by genetic factors and suggests a potential role for EAT in the development of hypertension.…”
Section: Children With Obesitymentioning
confidence: 99%